Asymmetric Synthesis of Trifluoromethyl-Containing Spiro[indoline-3,2′-pyrrolidine]s by Organocatalytic Cycloaddition - Cao, Yisheng; Shen, Zhiqiang; Zhang, Jingke; Chen, Haotian; Zhu, Wenbo; Han, Jian; Yan, Wenjin (Synthesis, 2025)
The unique biological activity of pyrrolidine compounds has attracted significant interest from medicinal chemists. This study presents a one-step synthesis of [indolyl-3,2′-pyrrolidine] compounds with three chiral centers and an α-CF3 group in excellent yields and enantioselectivities by reacting trifluoroethyl ketoimine with unsaturated alkynyl ketone compounds by a chiral-guanidine-catalyzed [3+2] cycloaddition reaction. The mild reaction conditions, low catalyst loading, and high reaction rate make this synthetic method highly attractive for pharmaceutical synthesis.
Keywords: asymmetric synthesis; trifluoromethyl-containing compounds; guanidine catalysis; spiropyrrolidines; [3+2] cycloaddition reaction